Simultaneous Determination of Cobalt (II) and Nickel (II) By First Order Derivative Spectrophotometry in Micellar Media. Issue 3 (2012) - Rohilla, Rajni; Gupta, Usha
Abstract : A first-derivative spectrophotometry method for the simultaneous determination of Co (II) and Ni (II) with Alizarin Red S in presence of Triton X-100 is described. Measurements were made at the zero-crossing wavelengths at 549.0 nm for Co (II) and 546.0 nm for Ni (II). The linearity is obtained in the range of 0.291- 4.676 μg/ml of Ni (II) and 0.293- 4.124 μg/ml of Co (II) in the presence of each other by using first derivative spectrophotometric method. The possible interfering effects of various ions were studied. The validity of the method was examined by using synthetic mixtures of Co (II) and Ni (II). The developed derivative procedure, using the zero crossing technique, has been successfully applied for the simultaneous analysis of Co (II) and Ni (II) in spiked water samples.